Electrolyte additive and preparation method thereof, electrolyte, battery with electrolyte and manufacturing method of battery
By using electrolyte additives with smaller polymer monomer molecular weight in lithium-ion batteries and combining with the SEI film formed by P element, the safety hazards and poor interface compatibility of lithium-ion batteries in high-power applications are solved, and better cycling performance and safety are achieved.
Patent Information
- Application Number
- CN202411854274.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
Existing lithium-ion batteries have safety risks in high-power applications, and the interface compatibility of all-solid electrolytes is poor and have high impedance, making it difficult to meet the battery usage requirements.
An electrolyte additive is provided, which has a small molecular weight of polymerized monomer, which can reduce interface impedance, improve interface compatibility, and form a Li3PO4-containing SEI film by introducing P elements to enhance the desolvation effect of lithium ions.
Effectively reduce interface impedance, improve interface compatibility, enhance the desolvation ability of lithium ions, and improve the circulation performance and safety of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium batteries, and more specifically, relates to an electrolyte additive and a preparation method thereof, an electrolyte, a battery having the electrolyte, and a manufacturing method thereof. Background Art
[0002] With the development of the times, the requirements for the capacity, safety and other performance of lithium-ion batteries are also increasing. The high power of the battery requires that the battery can provide instantaneous large current, that is, high-rate charge and discharge. Taking high-current discharge as an example, a large amount of Li is instantly generated on the surface of the negative electrode, diffused to the surface of the positive electrode in the electrolyte, and reacted on the surface of the positive electrode or inside the positive electrode to generate LiMO (M is a metal element). In recent years, with the development of portable electronic devices and the popularization of new energy vehicles, the demand for high energy density and high safety energy storage devices has become more and more urgent. Traditional batteries mostly use electrolytes, which have high ionic conductivity and charge and discharge efficiency, but the electrolyte is easy to leak, highly corrosive, flammable and explosive, which poses a great safety hazard to the battery. So the researchers turned their attention to all-solid-state batteries. The safety and stability of all-solid-state batteries have been significantly improved, and the cycle life is relatively long, but the interface compatibility of all-solid-state electrolytes is poor, the impedance is high, and the room temperature ionic conductivity is low, which makes it difficult to meet the battery requirements.
[0003] Gel electrolyte has the advantages of both electrolyte and all-solid electrolyte. While the safety is improved, the interface compatibility is also better than that of all-solid electrolyte, and the ionic conductivity is also improved accordingly. There have been many studies on the application of gel electrolyte in lithium-ion batteries and sodium-ion batteries. For example, the invention patent with publication number CN115241532A discloses electrolyte additives, electrolytes and lithium batteries. Increasing the difficulty of electrolyte penetration in pole pieces and diaphragms, improving wettability, and the interface compatibility between electrolyte and electrodes can improve the kinetics of ions and improve the cycle performance of batteries. Therefore, it is a direction that has always needed to be studied to develop electrolyte additives that can improve the above properties and apply them in electrolytes and batteries. Summary of the invention
[0004] The present application provides an electrolyte additive and a preparation method thereof, an electrolyte, a battery having the electrolyte and a manufacturing method thereof. The polymerized monomer has a small molecular weight and a small surface tension with the positive and negative electrodes of the battery, which effectively reduces the interface impedance and improves the interface compatibility. The ions can be coordinated with the polar functional groups introduced into the monomers. As the polymer chains move, the ions continuously jump from one coordination site to another, thereby realizing the transmission of ions and improving the cycle performance of the gel sodium ion battery.
[0005] To achieve the above-mentioned purpose, the technical solution of the present application provides an electrolyte additive, comprising at least one of the compounds represented by the following structural formulas I, II and III:
[0006] Structural formula Ⅰ:
[0007]
[0008] Structural formula Ⅱ:
[0009]
[0010] Structural formula III:
[0011]
[0012] In the structural formula I:
[0013] R1 and R3 are each independently selected from any one of hydrogen, a halogen atom, a nitro group, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 alkenyl group, a substituted or unsubstituted C2-C5 alkynyl group, and a substituted or unsubstituted C1-C5 alkoxy group;
[0014] R2 and R4 are each independently selected from any one of hydrogen, a halogen atom, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 alkenyl group, a substituted or unsubstituted C2-C5 alkynyl group, a substituted or unsubstituted C1-C5 alkoxy group, a nitro group, an amino group, a methoxy group, an ethoxy group, and a sulfonic acid group, or R2 and / or R4 have no substituent;
[0015] R5 is selected from any one of hydrogen, halogen atom, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C2-C5 alkenyl, substituted or unsubstituted C2-C5 alkynyl, or substituted or unsubstituted C1-C5 alkoxy, nitro, amino, methoxy, ethoxy, and sulfonic acid;
[0016] R6, R7 and R8 are each independently selected from any one of hydrogen or halogen atoms.
[0017] The technical solution of the present application provides a method for preparing the above-mentioned electrolyte additive, comprising substance A, substance B and catalyst Ni-CeO2, and adopting the following steps:
[0018] S1: Mix substance A, substance B and catalyst Ni-CeO2 in a molar ratio of (0.8-1.4):(0.6-1.3):(0.15-0.3), and stir at room temperature at 600-900 rpm for 50-70 min to obtain a product;
[0019] S2: Transfer the above product to an oven at 60-120°C and react for 12-48h;
[0020] S3: After the reaction, the upper clear liquid is taken, and the lower solid is washed with DMC to obtain a DMC solution. The supernatant is mixed with the DMC solution, and transferred to a flask, and heated in an oil bath at a heating rate of 3-20°C / min. The reaction product is collected from 80°C, and the collection is stopped when the temperature reaches 300°C to obtain a clear, transparent, colorless liquid;
[0021] S4: purifying the clear and transparent colorless liquid by distillation, collecting the final reaction product at 275-300° C., and determining the collected product to be the electrolyte additive by GC-MS;
[0022] in:
[0023] When the structural formula of substance A is A1, the structural formula of substance B is B1, and A1 and B1 are respectively:
[0024]
[0025] Or when the structural formula of substance A is A2, the structural formula of substance B is B2, and the A2 and B2 are respectively:
[0026]
[0027] Or when the structural formula of substance A is A3, the structural formula of substance B is B3, and the A3 and B3 are respectively:
[0028]
[0029] Or when the structural formula of substance A is A4, the structural formula of substance B is B4, and the A4 and B4 are respectively:
[0030]
[0031] Or when the structural formula of substance A is A5, the structural formula of substance B is B5, and the A5 and B5 are respectively:
[0032]
[0033] Or when the structural formula of substance A is A6, the structural formula of substance B is B6, and the A6 and B6 are respectively:
[0034]
[0035] The technical solution of the present application provides an electrolyte solution, comprising an electrolyte salt, an organic solvent, a first additive, a polymer monomer, a polymer initiator and the above-mentioned electrolyte additive.
[0036] Optionally, the electrolyte salt is selected from any one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide) and lithium bis(fluorosulfonylimide);
[0037] The organic solvent is selected from carbonate organic solvents and / or carboxylate organic solvents;
[0038] The first additive is selected from any one or more of vinylene carbonate, vinyl ethylene carbonate, vinyl acetate, vinyl sulfite, propylene sulfite, vinyl sulfate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, hexamethyldisilazane, magnesium imide trifluoromethanesulfonate, tris(pentafluorophenyl)boron, acetonitrile, dimethyl sulfoxide and acetic anhydride;
[0039] The polymer monomer is 1,3-dioxolane, and the polymer initiator is azobisisobutyronitrile.
[0040] Optionally, the organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, butyl propionate, ethyl butyrate and their halogenated derivatives.
[0041] Optionally, the mass content of the electrolyte salt is 10%-30%, the mass content of the organic solvent is 50%-70%, the mass content of the polymer monomer is 15%-25%, the mass content of the polymer initiator is 1%-4%, the mass percentage of the first additive is 1%-4%, and the mass percentage of the electrolyte additive is 1%-4%.
[0042] The technical solution of the present application provides a battery using the above-mentioned electrolyte.
[0043] Optionally, it also includes a positive electrode, a negative electrode and a separator; the active material of the positive electrode is lithium iron phosphate, and the active material of the negative electrode is composite graphite; the separator is selected from any one of a polyethylene separator, a polypropylene separator and a glass fiber separator.
[0044] The technical solution of the present application provides a method for manufacturing the above-mentioned battery, comprising the following steps:
[0045] S1: Select compacted lithium iron phosphate material as the positive electrode material, mix the compacted lithium iron phosphate, CNTs, and binder PVDF in a ratio of (95.5-96.5):(1.7-2.3):(1.7-2.3), apply it on the aluminum foil current collector, dry it in an oven, and roll it on a roller press. The compaction density is 2.35-2.55g / cm 3 , the required positive electrode sheet is obtained;
[0046] S2: Select compacted composite graphite as the negative electrode material, mix the composite graphite, CMC, conductive agent and binder in the ratio of (93.5-94.5):(0.8-1.2):(2.6-3.4):(1.7-2.3) to obtain a negative electrode sheet with a compacted density of 1.65-1.75 g / cm 3 ;
[0047] S3: Wind the positive electrode sheet and the negative electrode sheet, inject the electrolyte, and obtain the finished battery after formation and capacity separation.
[0048] The technical solution of this application has the following beneficial effects compared with the prior art:
[0049] The electrolyte additive for preparing gel polymer provided by the present application has a small molecular weight of the polymerized monomer and a small surface tension with the positive and negative electrodes of lithium / sodium ion batteries, which can make the composition fully wet the diaphragm, and can form a good interface contact with the electrode after polymerization, effectively reducing the interface impedance and improving the interface compatibility. At the same time, the P element introduced into the polymerized monomer forms a Li3PO4-containing SEI film on the surface of the graphite negative electrode, which significantly enhances the desolvation effect of Li+ in the electrolyte and effectively alleviates the co-embedding of solvent molecules.
[0050] This facilitation of desolvation not only helps reduce solvent decomposition at the negative electrode interface, but also supports the formation of SEI, which is of great value for quasi-solid-state batteries. It enables the gel polymer electrolyte to release free radicals at room temperature, which can capture oxygen free radicals generated by the decomposition of battery materials, making it difficult for the electrolyte to spontaneously combust.
[0051] In addition, sodium / lithium ions can coordinate with polar functional groups (such as F-, O-) introduced by the monomer. As the polymer chain moves, sodium / lithium ions continuously jump from one coordination site to another, realizing the transmission of sodium / lithium ions, thereby improving the cycle performance of gel sodium ion batteries. DETAILED DESCRIPTION
[0052] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0053] In the prior art, gel electrolytes mostly use macromolecular monomers with large molecular weight. When added to liquid electrolytes, the viscosity of the electrolyte will increase significantly, making it difficult for the electrolyte to penetrate into the electrode and the diaphragm after injection, and incomplete wetting is prone to occur, resulting in poor interface compatibility between the electrolyte and the electrode, high impedance, and thus affecting the cycle performance of the battery.
[0054] In view of this, the present application provides an electrolyte additive for preparing a gel polymer to solve the above problems. The electrolyte additive of the present application comprises at least one of all the compounds represented by the following structural formulas I, II and III:
[0055] Structural formula Ⅰ:
[0056]
[0057] Structural formula Ⅱ:
[0058]
[0059] Structural formula III:
[0060]
[0061] In the structural formula I:
[0062] R1 and R3 are each independently selected from any one of hydrogen, a halogen atom, a nitro group, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 alkenyl group, a substituted or unsubstituted C2-C5 alkynyl group, and a substituted or unsubstituted C1-C5 alkoxy group;
[0063] R2 and R4 are each independently selected from any one of hydrogen, a halogen atom, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 alkenyl group, a substituted or unsubstituted C2-C5 alkynyl group, a substituted or unsubstituted C1-C5 alkoxy group, a nitro group, an amino group, a methoxy group, an ethoxy group, and a sulfonic acid group, or R2 and / or R4 have no substituent;
[0064] R5 is selected from any one of hydrogen, halogen atom, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C2-C5 alkenyl, substituted or unsubstituted C2-C5 alkynyl, or substituted or unsubstituted C1-C5 alkoxy, nitro, amino, methoxy, ethoxy, and sulfonic acid;
[0065] R6, R7 and R8 are each independently selected from any one of hydrogen or halogen atoms.
[0066] It is understandable that no matter what substituents are selected for R1-R8 in structural formula I, or the substances in structural formula II and structural formula III are used, the P element is introduced into the polymerized monomer, and the SEI film containing Li3PO4 formed on the surface of the graphite negative electrode significantly enhances the desolvation of Li+ in the electrolyte and effectively alleviates the co-embedding of solvent molecules. From the subsequent test data of the battery, it can be shown that in the phosphorus-containing compounds of the present application, the SEI film containing P substances formed in the film-forming stage of the P group is the key group of the additive. Therefore, no matter what group R1 to R8 adopts within the above range, it does not affect the role of P. The above-mentioned electrolyte additives containing all types of groups from R1 to R8 are included in the protection scope of the present application, and do not affect the overall effect of P on the present application.
[0067] At the same time, due to the small molecular weight of the polymerized monomer and the small surface tension with the positive and negative electrodes of the lithium / sodium ion battery, the composition can fully wet the diaphragm, and after polymerization, it can form a good interface contact with the electrode, effectively reducing the interface impedance and improving the interface compatibility. This facilitation of desolvation not only helps to reduce the solvent decomposition at the negative electrode interface, but also supports the formation of SEI, which is of great value for quasi-solid-state batteries. Under normal temperature conditions, the gel polymer electrolyte can release free radicals, which can capture oxygen free radicals generated by the decomposition of battery materials, making it difficult for the electrolyte to spontaneously combust.
[0068] After the electrolyte additive is applied in the battery, the sodium / lithium ions can coordinate with the polar functional groups (such as F-, O-) introduced into the monomer. As the polymer chain moves, the sodium / lithium ions continuously jump from one coordination site to another, realizing the transmission of sodium / lithium ions, thereby improving the cycle performance of the gel sodium ion battery.
[0069] The present application is further described below in conjunction with examples. It should be understood that the examples provided in the present application are only to help understand the present application and should not be regarded as specific limitations to the present application.
[0070] Embodiment 1:
[0071] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A1 and a substance B with a structural formula of B1. The structural formula of the synthesized electrolyte additive is A-1. The structural formulas of A1, B1 and A-1 all refer to the following synthesis route of A-1. The synthesis route of A-1 is shown in the following formula:
[0072]
[0073] According to the above-mentioned synthesis route of A-1, the specific preparation method is as follows:
[0074] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 1.1:1:0.2 and stirred at 800 rpm for 60 min at room temperature;
[0075] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 120°C oven, and react for 24 hours;
[0076] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and transferred to a flask for oil bath heating at a heating rate of 5°C / min. The reaction product was collected starting from 80°C and stopped collecting when the temperature reached 300°C to obtain a clear, transparent, colorless liquid with a yield of nearly 50% and a purity of 85%.
[0077] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product in the temperature range of 290-300°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-1.
[0078] The mass spectrum data of the final product A-1 are TOF-MS (ESI) m / z calcd for C8H18FO2PSi: 224.29; [M+H]+found: 224.08.
[0079] Embodiment 2:
[0080] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A1 and a substance B with a structural formula of B1, and the synthesis route is the same as the synthesis route of A-1 in Example 1.
[0081] According to the above-mentioned synthesis route of A-1, the specific preparation method is as follows:
[0082] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 1.4:0.6:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0083] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0084] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, transferred to a flask, and heated in an oil bath at a heating rate of 10°C / min. The reaction product was collected from 80°C, and the collection was stopped when the temperature reached 300°C to obtain the reaction product. The vaporization temperature of the compound represented by formula A-1 was qualitatively determined by GC-MS to be between 275-285°C, and a clear and transparent colorless liquid was finally obtained with a yield of nearly 50% and a purity of 95%.
[0085] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-1.
[0086] Embodiment 3:
[0087] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A1 and a substance B with a structural formula of B1, and the synthesis route is the same as the synthesis route of A-1 in Example 1.
[0088] According to the above-mentioned synthesis route of A-1, the specific preparation method is as follows:
[0089] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 1.1:1.3:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0090] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0091] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, transferred to a flask, and heated in an oil bath at a heating rate of 3°C / min. The reaction product was collected from 80°C, and the collection was stopped when the temperature reached 300°C to obtain the reaction product. The vaporization temperature of the compound represented by formula A-1 was qualitatively determined by GC-MS to be between 275-285°C, and a clear and transparent colorless liquid was finally obtained with a yield of nearly 60% and a purity of 85%.
[0092] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-1.
[0093] Embodiment 4:
[0094] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A1 and a substance B with a structural formula of B1, and the synthesis route is the same as the synthesis route of A-1 in Example 1.
[0095] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.8:1.2:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0096] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0097] S3: After the reaction, the upper clear liquid is taken, and the lower solid is washed with DMC to obtain a DMC solution. The supernatant is mixed with the DMC solution, and the mixture is transferred to a flask for oil bath heating at a heating rate of 20°C / min. The reaction products are collected starting from 80°C, and the collection is stopped when the temperature reaches 300°C to obtain the reaction product. The vaporization temperature of the compound represented by formula A-1 is determined to be between 275°C and 285°C by GC-MS. Finally, a clear and transparent colorless liquid is obtained with a yield of nearly 60% and a purity of 95%.
[0098] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-1.
[0099] Embodiment 5:
[0100] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A1 and a substance B with a structural formula of B1, and the synthesis route is the same as the synthesis route of A-1 in Example 1.
[0101] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.9:1.1:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0102] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0103] S3: After the reaction, the upper clear liquid is taken, and the lower solid is washed with DMC to obtain a DMC solution. The supernatant is mixed with the DMC solution, and the mixture is transferred to a flask for oil bath heating at a heating rate of 5°C / min. The reaction products are collected starting from 80°C, and the collection is stopped when the temperature reaches 300°C to obtain the reaction product. The vaporization temperature of the compound represented by formula A-1 is qualitatively determined by GC-MS to be between 275-285°C. Finally, a clear, transparent, colorless liquid is obtained with a yield of nearly 50% and a purity of 85%.
[0104] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-1.
[0105] Embodiment 6:
[0106] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A2 and a substance B with a structural formula of B2. The structural formula of the synthesized electrolyte additive is A-2. The structural formulas of A2, B2 and A-2 all refer to the following synthesis route of A-2. The synthesis route of A-2 is shown in the following formula:
[0107]
[0108] According to the above-mentioned synthesis route of A-2, the specific preparation method is as follows:
[0109] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.8:1.2:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0110] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0111] S3: After the reaction, the upper clear liquid is taken, and the lower solid is washed with DMC to obtain a DMC solution. The supernatant is mixed with the DMC solution, and the mixture is transferred to a flask for oil bath heating at a heating rate of 20°C / min. The reaction products are collected starting from 80°C, and the collection is stopped when the temperature reaches 300°C to obtain the reaction product. The vaporization temperature of the compound represented by formula A-2 is determined to be between 275°C and 285°C by GC-MS. Finally, a clear and transparent colorless liquid is obtained with a yield of nearly 60% and a purity of 95%.
[0112] S4: Purify the clear and transparent colorless liquid by distillation, collect and obtain the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-2.
[0113] The mass spectrum data of product A-2 is TOF-MS (ESI) m / z calcd for C5H9F4O2PSi: 236.18; [M+H]+found: 236.00.
[0114] Embodiment 7:
[0115] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A2 and a substance B with a structural formula of B2, and the synthesis route is the same as the synthesis route of A-2 in Example 6.
[0116] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.9:1.1:0.2, and stirred at 600 rpm for 70 min at room temperature;
[0117] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 60°C oven, and react for 48 hours;
[0118] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and the mixture was transferred to a flask for oil bath heating at a heating rate of 8°C / min. The reaction products were collected starting from 80°C and stopped when the temperature reached 300°C. The vaporization temperature of the compound represented by formula A-2 was qualitatively determined by GC-MS to be between 275°C and 285°C. Finally, a clear, transparent, colorless liquid was obtained with a yield of nearly 56% and a purity of 87%.
[0119] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-2.
[0120] Embodiment 8:
[0121] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A3 and a substance B with a structural formula of B3. The structural formula of the synthesized electrolyte additive is A-3. The structural formulas of A3, B3 and A-3 all refer to the following synthesis route of A-3. The synthesis route of A-3 is shown in the following formula:
[0122]
[0123] According to the above-mentioned synthesis route of A-3, the specific preparation method is as follows:
[0124] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.8:1.2:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0125] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0126] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and the mixture was transferred to a flask for oil bath heating at a heating rate of 20°C / min. The reaction products were collected starting from 80°C and stopped when the temperature reached 300°C. The vaporization temperature of the compound represented by formula A-3 was qualitatively determined by GC-MS to be between 275-285°C. Finally, a clear and transparent colorless liquid was obtained with a yield of nearly 60% and a purity of 95%.
[0127] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-3.
[0128] The mass spectrum data of product A-3 are TOF-MS (ESI) m / z calcd for C7H15FNO4PSi: 255.26; [M+H]+found: 255.05.
[0129] Embodiment 9:
[0130] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A3 and a substance B with a structural formula of B3, and the synthesis route is the same as the synthesis route of A-3 in Example 8.
[0131] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 1.1:1.2:0.15, and stirred at 900 rpm for 50 min at room temperature;
[0132] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 120°C oven, and react for 12 hours;
[0133] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and the mixture was transferred to a flask for oil bath heating at a heating rate of 12°C / min. The reaction products were collected starting from 80°C and stopped when the temperature reached 300°C. The vaporization temperature of the compound represented by formula A-3 was qualitatively determined by GC-MS to be between 275°C and 285°C. Finally, a clear, transparent, colorless liquid was obtained with a yield of nearly 62% and a purity of 83%.
[0134] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-3.
[0135] Embodiment 10:
[0136] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A4 and a substance B with a structural formula of B4. The structural formula of the synthesized electrolyte additive is A-4. The structural formulas of A4, B4 and A-4 all refer to the following synthesis route of A-4. The synthesis route of A-4 is shown in the following formula:
[0137]
[0138] According to the above-mentioned synthesis route of A-4, the specific preparation method is as follows:
[0139] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.8:1.2:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0140] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0141] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and the mixture was transferred to a flask for oil bath heating at a heating rate of 20°C / min. The reaction products were collected starting from 80°C and stopped when the temperature reached 300°C. The vaporization temperature of the compound represented by formula A-4 was qualitatively determined by GC-MS to be between 275-285°C. Finally, a clear, transparent, colorless liquid was obtained with a yield of nearly 60% and a purity of 95%.
[0142] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-4.
[0143] The mass spectrum data of product A-3 are TOF-MS (ESI) m / z calcd for C5H10FO2P: 152.11; [M+H]+found: 152.04.
[0144] Embodiment 11:
[0145] This embodiment provides an electrolyte additive, which is prepared by using substance A with structural formula A4 and substance B with structural formula B4, and the synthesis route is the same as the synthesis route of A-4 in Example 10.
[0146] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.9:1.2:0.3, and stirred at 750 rpm for 65 min at room temperature;
[0147] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to an 80°C oven, and react for 24 hours;
[0148] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and the mixture was transferred to a flask for oil bath heating at a heating rate of 5°C / min. The reaction products were collected starting from 80°C and stopped when the temperature reached 300°C. The vaporization temperature of the compound represented by formula A-4 was qualitatively determined by GC-MS to be between 275-285°C. Finally, a clear, transparent, colorless liquid was obtained with a yield of nearly 52% and a purity of 87%.
[0149] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-4.
[0150] Embodiment 12:
[0151] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A5 and a substance B with a structural formula of B5. The structural formula of the synthesized electrolyte additive is A-5. The structural formulas of A5, B5 and A-5 all refer to the following synthesis route of A-5. The synthesis route of A-5 is shown in the following formula:
[0152]
[0153] According to the above-mentioned synthesis route of A-5, the specific preparation method is as follows:
[0154] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.8:1.2:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0155] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0156] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and the mixture was transferred to a flask for oil bath heating at a heating rate of 20°C / min. The reaction products were collected starting from 80°C and stopped when the temperature reached 300°C. The vaporization temperature of the compound represented by formula A-5 was qualitatively determined by GC-MS to be between 275-285°C. Finally, a clear, transparent, colorless liquid was obtained with a yield of nearly 60% and a purity of 95%.
[0157] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-5.
[0158] The mass spectrum data of product A-5 are TOF-MS (ESI) m / z calcd for C7H17OPSi: 176.27; [M+H]+ found: 176.08.
[0159] Embodiment 13:
[0160] This embodiment provides an electrolyte additive, which is prepared by using a substance A with a structural formula of A6 and a substance B with a structural formula of B6. The structural formula of the synthesized electrolyte additive is A-6. The structural formulas of A6, B6 and A-6 all refer to the following synthesis route of A-6. The synthesis route of A-6 is shown in the following formula:
[0161]
[0162] According to the above-mentioned synthesis route of A-5, the specific preparation method is as follows:
[0163] S1: Substance A, substance B and catalyst Ni-CeO2 were mixed in a molar ratio of 0.8:1.2:0.2, and stirred at 800 rpm for 60 min at room temperature;
[0164] S2: Use a stainless steel reactor shell to encapsulate the Teflon reactor, transfer it to a 70°C oven, and react for 24 hours;
[0165] S3: After the reaction, the upper clear liquid was taken, and the lower solid was washed with DMC to obtain a DMC solution. The supernatant was mixed with the DMC solution, and the mixture was transferred to a flask for oil bath heating at a heating rate of 20°C / min. The reaction products were collected starting from 80°C and stopped when the temperature reached 300°C. The vaporization temperature of the compound represented by formula A-6 was qualitatively determined by GC-MS to be between 275-285°C. Finally, a clear and transparent colorless liquid was obtained with a yield of nearly 60% and a purity of 95%.
[0166] S4: Purify the clear and transparent colorless liquid by distillation, collect the final reaction product at 275-285°C, and characterize it by GC-MS to determine that the collected final product is the compound represented by formula A-6.
[0167] The mass spectrum data of product A-6 are TOF-MS (ESI) m / z calcd for C8H17F2O2PSi: 242.28; [M+H]+found: 242.07.
[0168] It can be seen from the synthesis routes of Examples 1-13 that, regardless of the electrolyte additive, in order to achieve a reaction product with a corresponding yield and purity, the rotation speed in step S1 and the stirring time are negatively correlated as a whole, and the drying temperature of the oven and the reaction time in step S2 are negatively correlated. Within the range of the heating rate specified in this application, the heating rate has little to do with the yield and purity of the final product.
[0169] At the same time, the technical solution of the present application provides an electrolyte solution, including an electrolyte salt, an organic solvent, a first additive, a polymer monomer, a polymer initiator and the above-mentioned electrolyte additive.
[0170] Specifically, the electrolyte salt is selected from any one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide) and lithium bis(fluorosulfonylimide);
[0171] The organic solvent is selected from carbonate organic solvents and / or carboxylate organic solvents;
[0172] The first additive is selected from any one or more of vinylene carbonate, vinyl ethylene carbonate, vinyl acetate, vinyl sulfite, propylene sulfite, vinyl sulfate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, hexamethyldisilazane, magnesium imide trifluoromethanesulfonate, tris(pentafluorophenyl)boron, acetonitrile, dimethyl sulfoxide and acetic anhydride;
[0173] The polymer monomer is 1,3-dioxolane, and the polymer initiator is azobisisobutyronitrile. The polymer initiator initiates a polymerization reaction of the polymer monomer to form a polymer.
[0174] Wherein, the organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, butyl propionate, ethyl butyrate and their halogenated derivatives.
[0175] Among them, the mass content of the electrolyte salt is 10%-30%, the mass content of the organic solvent is 50%-70%, the mass content of the polymer monomer is 15%-25%, the mass content of the polymer initiator is 1%-4%, the mass percentage of the first additive is 1%-4%, and the mass percentage of the electrolyte additive is 1%-4%.
[0176] The electrolyte salt, organic solvent, first additive, polymer monomer, polymer initiator and electrolyte additive are prepared by reasonable combination according to the requirements of the reaction product. The electrolytes in the following preferred embodiments 14 to 33 and comparative examples 1 and 2 are prepared according to the following method:
[0177] In a glove box filled with argon gas to a purity of 99.999% and with environmental indicators of H2O≤0.1ppm and O2≤0.1ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), 1,3-dioxolane (DOL), azobisisobutyronitrile (AIBN), electrolyte additives, and vinylene carbonate (VC) are uniformly mixed, and then lithium hexafluorophosphate (LiPF6) is added and mixed thoroughly to form a lithium hexafluorophosphate electrolyte solution, i.e., the above-mentioned electrolyte.
[0178] The contents of each component in Examples 14-33, Comparative Examples 1 and 2, and the electrolyte conductivity data are shown in Table 1 below. In Table 1, the contents of each component are all mass percentages calculated based on the total mass of the electrolyte. Examples 14-27 contain only one structural electrolyte additive, and Examples 28-33 contain two structural electrolyte additives.
[0179] In order to control variables to achieve comparison of effects between different electrolyte additives and after mixing of electrolyte additives, the mass percentages of ethylene carbonate (EC), 1,3-dioxolane (DOL), azobisisobutyronitrile (AIBN) and lithium hexafluorophosphate (LiPF6) in Examples 14-33, Comparative Examples 1 and 2 are the same, and only the ethyl methyl carbonate (EMC) in the organic solvent is changed to balance the electrolyte additives of different concentrations.
[0180] Among them, the structural formula B-1 of the electrolyte additive in Comparative Example 2 is as follows:
[0181]
[0182] It should be understood that the embodiments provided in this application are only to help understand this application and should not be regarded as specific limitations of this application.
[0183] Table 1
[0184]
[0185]
[0186] According to the experimental results of Examples 14-27, it can be found that the electrolyte additives with structural formulas A-1 to A-6 provided in the present application have a better effect on improving conductivity than the electrolyte additive with structural formula B-1 at the same mass percentage, and are better than the case where no electrolyte additive is added. The conductivity of the above-mentioned in-situ polymerized electrolyte is tested after polymerization, which reflects the desolvation ability of lithium ions during the charge and discharge process of the battery. The higher the conductivity, the stronger the desolvation ability.
[0187] By comparing Examples 14-17, Examples 18 and 19, Examples 20 and 21, Examples 22 and 23, Examples 24 and 25, and Examples 26 and 27, it can be seen that within the concentration range of the present application, the higher the concentration of the electrolyte additive, the higher the conductivity of the electrolyte will be.
[0188] At the same time, through the above data, it can be found that the improvement effect of the electrolyte additives with structural formulas A-1 and A-3 is also better. Among them, the effect of the electrolyte additive with a mass concentration of only 1% in Example 14 is already ahead of the effect of the electrolyte additives with structural formulas A-2, A-4, A-5 and A-6 at a concentration of 2%. It shows that the electrolyte additive with structural formula A-1 has a strong ability to assist lithium ions in desolvation during the battery charging and discharging process. The improvement effect of the electrolyte additive with structural formula A-3 is better than the improvement effect of the electrolyte additive with structural formula A-1 at the same concentration. It can be inferred that it is due to the effect of the nitro group.
[0189] According to the experimental results of Examples 28-33, it can be found that when electrolyte additives with different structural formulas are mixed, the electrolyte conductivity is also improved relative to Comparative Example 1 and Comparative Example 2, and the improved value is basically equal to the weighted average of the corresponding single structural electrolyte additive, with only fluctuations within the error range.
[0190] The combination and proportion of the above-mentioned other electrolyte salts, organic solvents, first additives, polymer monomers, polymer initiators and electrolyte additives are described below through preferred Examples 34-43 and Comparative Examples 3-4, with specific reference to Table 2. It should be noted that the types and concentrations of substances are not strictly controlled in the following Examples 34-43, and some conclusions are only trend conclusions.
[0191] The electrolytes in Examples 34-43 and Comparative Examples 3-4 were prepared according to the following method:
[0192] In a glove box filled with argon gas to a purity of 99.999% and with environmental indicators of H2O≤0.1ppm, O2≤0.1ppm, the electrolyte salt, organic solvent, first additive, polymer monomer, polymer initiator and electrolyte additive are fully mixed to form an electrolyte solution, namely the above-mentioned electrolyte.
[0193] Table 2
[0194]
[0195]
[0196] According to the experimental results of Examples 34-43, and in combination with the experimental results of Examples 14-33 in Table 1 above, it can be seen that the electrolyte additives with structural formulas A-1 to A-6 provided in the present application and their combinations have an effect on improving conductivity that is better than the electrolyte additive with structural formula B-1 at the same mass percentage, and is better than the case where no electrolyte additive is added. At the same time, for the electrolyte additive with structural formula A-1 having a mass concentration of only 1% in Examples 34 and 42, its effect is already ahead of the effects of other electrolyte additives with higher concentrations in Examples 35, 40, and 41. It also proves that the electrolyte additive with structural formula A-1 has a strong ability to assist lithium ions in desolvation during battery charging and discharging. And the conductivity of the electrolyte with the electrolyte additive with structural formula A-3 in Example 36 reached the maximum value among all the embodiments of the present application, and the effect is equally excellent.
[0197] From Example 14 and Example 42, when the concentrations of other substances are the same, the concentration of electrolyte salt is positively correlated with the conductivity, which is analyzed to be due to the increase in ion concentration in the electrolyte salt. For organic solvents composed of different substances, in the range of the present application, since the chemical properties of the substances that can be selected by the organic solvent are relatively similar, it is expected that the effect on the conductivity of the electrolyte is small. It should be noted that since the types of substances in the comparative examples are not strictly controlled variables, only trend judgments are made.
[0198] And within the numerical range of the present application, from the comparison of Example 20 and Example 36, within the range defined in the present application, the higher the mass percentage of the polymer monomer, the higher the electrolyte conductivity. And from the data of Example 24 and Example 40, it can be seen that when the mass percentage of the polymer monomer and the polymer initiator are the same, the electrolyte conductivity difference is not large, which further proves the effect of the above-mentioned polymer monomer on the electrolyte conductivity. At the same time, from the comparison of Example 26 and Example 41, although the mass percentage of the polymer monomer in Example 41 increases, the conductivity decreases due to the lower mass percentage of the polymer initiator. It can be inferred that within the numerical range defined in the present application, the concentration of the polymer initiator is also positively correlated with the conductivity, and the influence is relatively large. In fact, since the polymer initiator is used to initiate the polymerization reaction of the polymer monomer to form a polymer. It is foreseeable that the concentration of the polymer initiator has a greater impact. It should be noted that due to the slight difference in the types and concentrations of the substances in the above-mentioned embodiments compared with each other, there is no strict control variable, and only a trend judgment is made.
[0199] From the comparison of the data of Example 16 and Example 37, it can be seen that as the concentration of the first additive increases, the conductivity of the electrolyte will also increase, but the conductivity data in Example 37 is still greater than the conductivity data of the electrolyte additive with a lower concentration in Example 15. Therefore, the effect of the first additive on the conductivity is less than the effect of the electrolyte additive on the conductivity.
[0200] Similarly, when electrolyte additives of different structural formulas are mixed, the electrolyte conductivity is also improved relative to Comparative Example 3 and Comparative Example 4, and the improved value is basically equal to the weighted average of the corresponding single structural electrolyte additive, with only fluctuations within the error range.
[0201] It can be concluded that in the electrolyte of the present application, within the specified range of the present application, the concentration of the electrolyte salt, the type and concentration of the electrolyte additive, the polymer monomer concentration, the concentration of the polymer initiator and the concentration of the first additive have a greater influence on the conductivity of the electrolyte, while the type and concentration of the organic solvent have a smaller influence on the conductivity.
[0202] Embodiment 44:
[0203] The technical solution of the present application provides a battery, which adopts any of the above-mentioned electrolytes. In detail, the battery also includes a positive electrode, a negative electrode and a separator. The active material of the positive electrode is lithium iron phosphate, and the active material of the negative electrode is composite graphite. The separator is selected from any one of a polyethylene separator, a polypropylene separator and a glass fiber separator. Among them, lithium iron phosphate, composite graphite, polyethylene separator, polypropylene separator and glass fiber separator are all common materials in lithium batteries, which will not be repeated here. The specific improvement is to replace the electrolyte with the electrolyte of this application.
[0204] After the electrolyte additive is added to the electrolyte, the molecular weight of the polymerized monomer is small, and the surface tension with the positive and negative electrodes of the battery is small, which can effectively reduce the interfacial impedance and improve the interfacial compatibility. The P element introduced into the polymerized monomer forms a Li3PO4-containing SEI film on the surface of the graphite negative electrode, which significantly enhances the desolvation of lithium ions in the electrolyte and effectively alleviates the co-embedding of solvent molecules. Under normal temperature conditions, the gel polymer electrolyte can release free radicals and capture oxygen free radicals produced by the decomposition of battery materials, and the electrolyte is difficult to self-ignite; ions can coordinate with the polar functional groups introduced by the monomer. As the polymer chain moves, the ions continuously jump from one coordination site to another, realizing ion transmission and improving the cycle performance of the gel sodium ion battery.
[0205] Embodiment 45:
[0206] The present application also provides a method for manufacturing the battery in Example 44, which specifically comprises the following steps:
[0207] S1: Select compacted lithium iron phosphate material as the positive electrode material, mix the compacted lithium iron phosphate, CNTs, and binder PVDF in a ratio of 96:2:2, coat it on the aluminum foil current collector, dry it in an oven, and roll it on a roller press. The compaction density is 2.5g / cm 3 , the required positive electrode sheet is obtained and the electrolyte wettability test is performed on it.
[0208] S2: Select compacted composite graphite as the negative electrode material, mix the composite graphite, CMC, conductive agent and binder in a ratio of 94:1:3:2 to obtain a negative electrode sheet with a compacted density of 1.7 g / cm 3 ;
[0209] S3: Winding the positive electrode sheet and the negative electrode sheet, injecting the electrolytes in Examples 14-27 and Comparative Examples 1-2, and obtaining a finished battery after formation and capacity separation.
[0210] The electrical performance of the battery prepared by the above method is now tested at a room temperature of 25°C. Three soft packs are taken for each test and the test results are averaged. The specific test method is as follows:
[0211] After the soft pack is filled with liquid, the rated capacity is 2.5Ah and the filling coefficient is 6g / Ah. After the filling, it is formed, aged, and divided. After standing, three soft packs with similar capacity are selected to calculate the first effect, test the internal resistance and open circuit voltage, and then transferred to the constant temperature test room with a fixture, the voltage range is 2.5-3.65V, and the 1C cycle test is performed for 500 weeks.
[0212] The battery is formed according to the following steps: 0.1C constant current charging to 3.0V, 0.2C constant current charging to 3.3V, the formed battery is first aged, then vacuum sealed, and then capacity divided according to the following steps: 0.5C constant current discharge to 2.5V, 0.5C constant current constant voltage charging to 3.65V, constant current discharge to 2.5V, cross-current charging to 3.3V, first effect = (constant current discharge total capacity / constant current constant voltage charging capacity + formation charging capacity) * 100%.
[0213] According to the above method, the test data of the battery is shown in Table 3 below:
[0214] Table 3
[0215]
[0216] It can be seen from the example data in Table 1 and Table 3 that, compared with the data of Comparative Examples 1 and 2, when the electrolyte additive of the present application is added to the electrolyte, the desolvation ability of lithium ions is improved during the charge and discharge process, the internal resistance of the battery has an overall downward trend, and the high-rate discharge capacity retention rate is improved, and the first efficiency and cycle performance are also improved to a certain extent.
[0217] By comparing the experimental data of Examples 14-17, it can be found that when the structural formula of the electrolyte additive is A-1 and the addition amount is 2%, the electrochemical performance of the lithium iron phosphate / graphite soft pack system is improved to the highest degree, and under the same formation cut-off voltage limit conditions, the battery capacity is high, indicating that the desolvation ability of the polymer electrolyte is improved, the capacity is exerted in the first cycle, and the cycle life at room temperature is good, which plays a positive role in promoting the desolvation of lithium ions.
[0218] By comparing Example 15 with Example 18, after the trimethylsilyl group on the structural formula A-1 increases with the F-containing substituent group and the structural formula becomes A-2, the number of electron-withdrawing groups increases, resulting in a certain limitation in the desolvation ability of lithium ions during the battery charge and discharge process, indicating that the introduction of electron-withdrawing groups fails to promote the desolvation ability of lithium ions during the battery charge and discharge process.
[0219] Through the data analysis of Example 15, Example 18, Example 26 and Comparative Example 2, it can be found that the fluorinated group does not have a positive effect on the conductivity of the electrolyte as the substitution position changes. In Comparative Example 2, which introduces the commercially available desolvation additive molecular formula B-1, the conductivity shows a significant decrease after removing the trimethylsilyl group and the P-containing group. Through the electrolyte conductivity data of the above embodiments, we find that when the positions of the P group and the O group are fixed, changing the substitution position and number of the electron-withdrawing group -F has a smaller effect on the conductivity of the electrolyte than the effect of the P group and the O group, and the capacity of the first cycle of charge and discharge is not significantly improved, indicating that in the phosphorus-containing compounds of the present application, the SEI film containing the P group and the P substance formed in the film-forming stage is the key group of the additive.
[0220] By comparing Example 15 with Example 22, it is found that after removing the trimethylsilyl group, adding Example 22 of the molecular formula A-4, the conductivity of the electrolyte decreases, but the decrease is relatively small and basically remains constant. However, the comparison of the electrochemical performance of the soft pack shows that the internal resistance of the soft pack increases, the cycle performance decreases, and the combined capacity is exerted. This is because the trimethylsilyl group does not participate in the film formation in the initial film formation stage, resulting in the lack of inorganic components in the components of the SEI film, an increase in impedance, and finally a decrease in the later cycle life.
[0221] By comparing Example 20 with Example 15, we found that by adding a new nitro group to the new molecular formula, the introduction of an electron-withdrawing group increased the conductivity of the electrolyte, but slightly reduced the discharge capacity during the initial charge and discharge process, and in the later stages of the cycle, due to the problem that the nitrogen-containing group and the F group compete for the film-forming sites during the SEI film formation process, the components of the SEI film in the film-forming stage are mainly nitrogen-containing components. The stability of the SEI film will decline to a certain extent in the later stages, and the 1C cycle life at room temperature will be affected to a certain extent. Therefore, it is found that the introduction of nitrogen-containing groups needs to be controlled to a certain extent.
[0222] For step S1 in the above embodiment 45, the ratio of high-density lithium iron phosphate, CNTs, and binder PVDF in the positive electrode material can also be set to any value in the range of (95.5-96.5):(1.7-2.3):(1.7-2.3) according to actual conditions, and the compaction density is 2.35-2.55 g / cm 3 The ratio of composite graphite, CMC, conductive agent, and binder in step S2 can also be set to any value in the range of (93.5-94.5):(0.8-1.2):(2.6-3.4):(1.7-2.3) according to actual conditions to obtain a negative electrode sheet with a compaction density of 1.65-1.75 g / cm 3 , and batteries with expected effects can be obtained.
[0223] Finally, the test method of electrolyte conductivity in Table 1 and Table 2 is supplemented, specifically the test method of electrolyte conductivity in gel state after polymerization, and the steps are as follows:
[0224] Insert the cleaned electrode into the calibration solution, making sure the electrode is completely submerged in the solution and there are no bubbles attached to the electrode tip.
[0225] Follow the calibration steps of the DDS-11A conductivity meter. Usually, first set the conductivity meter to calibration mode, then enter the conductivity value of the calibration solution according to the instrument prompts, and wait for the instrument to automatically calibrate.
[0226] During the calibration process, observe the display of the conductivity meter to ensure that the calibration value is stable and within the allowable error range. If the calibration result is beyond the error range, repeat the calibration operation or check whether there is a problem with the electrode and calibration solution.
[0227] After calibration, insert the electrode into the electrolyte, which needs to be in-situ polymerized and in a gel state. Make sure the electrode is completely immersed in the electrolyte and there are no bubbles between the electrodes when inserting. If there are bubbles, it may cause inaccurate measurement results. You can gently shake the electrode or electrolyte container to remove the bubbles. Wait for the conductivity tester reading to stabilize. This may take from a few seconds to a few minutes, depending on the model of the conductivity tester and the properties of the electrolyte. Read and record the conductivity value displayed by the conductivity tester. Some conductivity testers can also display temperature values. If temperature compensation is required, it can be operated according to the instrument manual.
[0228] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An electrolyte additive, characterized in that: Contains at least one of the compounds represented by the following structural formulas Ⅰ, Ⅱ and Ⅲ: Structural formula Ⅰ: Structural formula Ⅱ: Structural formula III: In the structural formula I: R1 and R3 are each independently selected from any one of hydrogen, a halogen atom, a nitro group, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 alkenyl group, a substituted or unsubstituted C2-C5 alkynyl group, and a substituted or unsubstituted C1-C5 alkoxy group; R2 and R4 are each independently selected from any one of hydrogen, a halogen atom, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 alkenyl group, a substituted or unsubstituted C2-C5 alkynyl group, a substituted or unsubstituted C1-C5 alkoxy group, a nitro group, an amino group, a methoxy group, an ethoxy group, and a sulfonic acid group, or R2 and / or R4 have no substituent; R5 is selected from any one of hydrogen, halogen atom, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C2-C5 alkenyl, substituted or unsubstituted C2-C5 alkynyl, or substituted or unsubstituted C1-C5 alkoxy, nitro, amino, methoxy, ethoxy, and sulfonic acid; R6, R7 and R8 are each independently selected from any one of hydrogen or halogen atoms.
2. The method for preparing the electrolyte additive as claimed in claim 1, characterized in that: The method comprises a substance A, a substance B and a catalyst Ni-CeO2, and adopts the following steps: S1: Mix substance A, substance B and catalyst Ni-CeO2 in a molar ratio of (0.8-1.4):(0.6-1.3):(0.15-0.3), and stir at room temperature at 600-900 rpm for 50-70 min to obtain a product; S2: Transfer the above product to an oven at 60-120°C and react for 12-48h; S3: After the reaction, the upper clear liquid is taken, and the lower solid is washed with DMC to obtain a DMC solution. The supernatant is mixed with the DMC solution, and transferred to a flask, and heated in an oil bath at a heating rate of 3-20°C / min. The reaction product is collected from 80°C, and the collection is stopped when the temperature reaches 300°C to obtain a clear, transparent, colorless liquid; S4: purify the clear and transparent colorless liquid by distillation and collect at 275-300°C to obtain the final reaction product; in: When the structural formula of substance A is A1, the structural formula of substance B is B1, and A1 and B1 are respectively: Or when the structural formula of substance A is A2, the structural formula of substance B is B2, and the A2 and B2 are respectively: Or when the structural formula of substance A is A3, the structural formula of substance B is B3, and the A3 and B3 are respectively: Or when the structural formula of substance A is A4, the structural formula of substance B is B4, and the A4 and B4 are respectively: Or when the structural formula of substance A is A5, the structural formula of substance B is B5, and the A5 and B5 are respectively: Or when the structural formula of substance A is A6, the structural formula of substance B is B6, and the A6 and B6 are respectively:
3. An electrolyte, characterized in that: The invention comprises an electrolyte salt, an organic solvent, a first additive, a polymer monomer, a polymer initiator and the electrolyte additive as claimed in claim 1 or 2.
4. The electrolyte according to claim 3, characterized in that: The electrolyte salt is selected from any one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide) and lithium bis(fluorosulfonylimide); The organic solvent is selected from carbonate organic solvents and / or carboxylate organic solvents; The first additive is selected from any one or more of vinylene carbonate, vinyl ethylene carbonate, vinyl acetate, vinyl sulfite, propylene sulfite, vinyl sulfate, 1,3-propane sultone, 1,4-butane sultone, methylene disulfonate, hexamethyldisilazane, magnesium imide trifluoromethanesulfonate, tris(pentafluorophenyl)boron, acetonitrile, dimethyl sulfoxide and acetic anhydride; The polymer monomer is 1,3-dioxolane, and the polymer initiator is azobisisobutyronitrile.
5. The electrolyte according to claim 4, characterized in that: The organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, butyl propionate, ethyl butyrate and their halogenated derivatives.
6. The electrolyte according to claim 4 or 5, characterized in that: The mass content of the electrolyte salt is 10%-30%, the mass content of the organic solvent is 50%-70%, the mass content of the polymer monomer is 15%-25%, the mass content of the polymer initiator is 1%-4%, the mass percentage of the first additive is 1%-4%, and the mass percentage of the electrolyte additive is 1%-4%.
7. A battery, characterized in that: An electrolyte as described in claim 3, 4, 5 or 6 is used.
8. The battery as claimed in claim 7, characterized in that: It also includes a positive electrode, a negative electrode and a separator; the active material of the positive electrode is lithium iron phosphate, and the active material of the negative electrode is composite graphite; the separator is selected from any one of a polyethylene separator, a polypropylene separator and a glass fiber separator.
9. The method for manufacturing a battery according to claim 7 or 8, characterized in that: The steps include: S1: Select compacted lithium iron phosphate material as the positive electrode material, mix the compacted lithium iron phosphate, CNTs, and binder PVDF in a ratio of (95.5-96.5):(1.7-2.3):(1.7-2.3), apply it on the aluminum foil current collector, dry it in an oven, and roll it on a roller press. The compaction density is 2.35-2.55g / cm 3 , the required positive electrode sheet is obtained; S2: Select compacted composite graphite as the negative electrode material, mix the composite graphite, CMC, conductive agent and binder in the ratio of (93.5-94.5):(0.8-1.2):(2.6-3.4):(1.7-2.3) to obtain a negative electrode sheet with a compacted density of 1.65-1.75 g / cm 3 ; S3: Wind the positive electrode sheet and the negative electrode sheet, inject the electrolyte, and obtain the finished battery after formation and capacity separation.
Citation Information
Patent Citations
Electrolyte additive, electrolyte and lithium battery
CN115241532A
